Optimization of Restaurant Tax Revenue in Increasing Local Original Income of Gowa Regency - Muhammad Khaedar Sahib; Muhaimin Muhaimin; Andi Mifta Putri Wulansari (Universitas Muhammadiyah Makassar, 2024)
The purpose of this research is to find out the optimization of restaurant tax revenue in increasing the original income of Gowa Regency and to find out the contribution of restaurant tax in the original income of Gowa Regency. The object of this final project research is